Inhibin A—A Promising Predictive Parameter for Determination of Final Oocyte Maturation in Ovarian Stimulation for IVF/ICSI - Lawrenz, Barbara; Depret Bixio, Leyla; Coughlan, Carol; Andersen, Claus Yding; Melado, Laura; Kalra, Bhanu; Savjani, Gopal; Fatemi, Human M.; Kumar, Ajay (Frontiers in Endocrinology, 2020)
The number of mature oocytes is a key factor in the success of Assisted Reproductive Techniques (ART). Exogenous gonadotropins are administered during ovarian stimulation in order to maximise the number of oocytes available for fertilization. During stimulation, monitoring is mandatory to evaluate individual response, to avoid treatment complications and assist in the determination of the optimal day for final oocyte maturation and oocyte retrieval. Routine monitoring during stimulation includes transvaginal ultrasound examinations and measurement of serum estradiol (E2). Due to multifollicular growth of follicles of varying size, serum E2 levels are commonly supraphysiological and often variable, rendering E2-measurement during ovarian stimulation unreliable as a determinant of oocyte maturity. In contrast to serum E2, serum Inhibin A levels increase once a minimum follicle size of 12-15 mm is achieved. Due to this fact, serum Inhibin A levels could present in combination with ultrasound monitoring a more reliable parameter to determine the optimal follicle size for final oocyte maturation, as only follicles with a size of 12 mm and beyond will contribute to the serum Inhibin A level. This prospective observational, cross-sectional study demonstrates, that on the day of final oocyte maturation serum Inhibin A is strongly correlated to the number of follicles ≥ 15 mm (0.72) and to the number of retrieved and mature oocytes (ρ 0.82 / 0.77, respectively), whereas serum E2 is moderately correlated to the parameters mentioned above (ρ 0.64 / 0.69 / 0.69, respectively). With an area under the curve (AUC) of 0.91 for Inhibin A, compared to an AUC of 0.84 for E2, Inhibin A can be regarded as a better predictor for the optimal timing of trigger medication with a threshold number of ≥ 10 mature oocytes. It can be concluded from this data that serum Inhibin A in combination with transvaginal ultrasound monitoring may be a more powerful tool in the decision making process on trigger timing as compared to E2.